EWA-Evaluation web accessibility - Fernandes, Nádia Raquel Palma (2011)
The purpose of this work was to improve the automated Web accessibility evaluation, considering that: evaluation should target what the end users perceive and interact with; evaluation results should address accessibility problems in a focused, uncluttered, way; and results should reflect the quality adequately to the stakeholders.